Inside front cover: Dietary emulsifiers from milk and soybean differently impact adiposity and inflammation in association with modulation of colonic goblet cells in high‐fat fed mice. Issue 3 (3rd March 2016) - Lecomte, Manon; Couëdelo, Leslie; Meugnier, Emmanuelle; Plaisancié, Pascale; Létisse, Marion; Benoit, Bérengère; Gabert, Laure; Penhoat, Armelle; Durand, Annie; Pineau, Gaëlle; Joffre, Florent; Géloën, Alain; et al.
Abstract : Mol. Nutr. Food Res . 2016, 60, 609–620. DOI:10.1002/mnfr.201500703 The effects of polar lipid emulsifiers from milk (MPL) versus soybean (SPL) were investigated in high‐fat (HF) fed mice. Compared with an HF‐SPL diet, which induced increased expression of inflammation markers in white adipose tissue, an HF‐MPL diet induced a lower expression of macrophage infiltration markers in white adipose tissue associated with a greater number of mucus‐producing goblet cells in the colon.